Potensi Ekstrak Ubi Gadung (Dioscorea hispida Dennst.) dan Ekstrak Gulma Babadotan (Ageratum conyzoides L.) untuk Pengendalian Hama Penghisap Buah Kakao (Helopeltis spp.) di Laboratorium - Supriyatdi, Dedi; Fernando, Adam; Sari, Sismita (Politeknik Negeri Lampung, 2022)
Cocoa pod sucking (Helopeltis spp.) is one of the pests that causes a productivity decrease of cocoa pod in Indonesia. In terms of control, many farmers in Indonesia are still using synthetic insecticides that are not environmentally friendly, so intoxicating yam (Dioscorea hispida Dennts) and tropical whiteweed (Ageratum conyzoides L.) are used as botanical insecticide that are environmentally friendly. The objective of this research is to determine the effect of botanical insecticide that made of intoxicating yam extract, tropical whiteweed extract, and mixed extract of intoxicating yam and tropical whiteweed on the mortality of cocoa pod sucking pests. This research was carried out from November 2020 to February 2021, at the Plant Laboratory II Estate Crop Department, Politeknik Negeri Lampung. The research used a Randomized Block Design (RBD) consisting of four treatments, namely: P0 (control), P1 (intoxicating yam extract), P2 (tropical whiteweed extract), and P3 (combination of both extracts), which were repeated six times. The highest mortality of cocoa pod sucking pests was found in treatment P1 (72.73%). The mortality of cocoa pod sucking pest was caused by extract of intoxicating yam which contains the active ingredients of saponins, alkaloids, flavonoids, and cyanide which enter the digestive system of the cocoa pod sucking pest as stomach poisons, resulting in the death of the cocoa pod sucking pest. Based on the results of the research, it was concluded that intoxicating yam extract is the most potential as botanical insectiside for cocoa pod sucking pest.